(untitled) (Bangladesh Journal of Pharmacology, 2011)
Herbal medicines are being used for the treatment of different diseases for centuries. Sustainable development of herbal medicines need the study of their safety, efficacy and standardization are essential. Two commercially available herbal medicines i.e., Ziabetes (dolabi) and Jambadayrist, and a folkloric medicine prepared from four plant materials by a local practitioners were investigated for their chemical compositions. Four compounds were isolated from the extracts of these medicines by silica gel column chromatography. Oleic acid and p-hydroxycinnamic acid were isolated from the aqueous 80%ethanol extract of the folkloric medicine whereas benzoic acid was found to be present in Ziabetes and Jambadayrist. The present investigation revealed that excessive amount of benzoic acid (or sodium benzoate) is being added as preservative in commercial herbal medicines.